2007
DOI: 10.1086/510742
|View full text |Cite
|
Sign up to set email alerts
|

The Swan System of C 2 : A Global Analysis of Fourier Transform Emission Spectra

Abstract: The C 2 Swan system (d 3 Å g -a 3 Å u ) was observed in emission for the Áv ¼ À3 to Áv ¼ þ2 sequences in the 14,000Y 24,000 cm À1 spectral range using a Fourier transform spectrometer. We carried out a global simultaneous fit by including a wide range of vibrational states. A total of 34 bands with v 0 ¼ 0Y10 and v 00 ¼ 0Y9 were rotationally assigned. Numerous discrepancies were found in the assignments and in the measured transition wavenumbers between the new measurements and previous results. Most of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
94
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(112 citation statements)
references
References 53 publications
17
94
1
Order By: Relevance
“…A recent study of the d 3 P g À c 3 R þ u system by Joester et al [27] revealed perturbations in the d 3 P g ; v 0 ¼ 4 level. The supersonically cooled radicals exhibiting only low J levels and, therefore, less congestion disclose perturbations that are in significant disagreement with the reported values from Tanabashi et al [20,25].…”
Section: Introductioncontrasting
confidence: 55%
See 3 more Smart Citations
“…A recent study of the d 3 P g À c 3 R þ u system by Joester et al [27] revealed perturbations in the d 3 P g ; v 0 ¼ 4 level. The supersonically cooled radicals exhibiting only low J levels and, therefore, less congestion disclose perturbations that are in significant disagreement with the reported values from Tanabashi et al [20,25].…”
Section: Introductioncontrasting
confidence: 55%
“…The bands are denoted by the standard nomenclature ðv 0 ; v 00 Þ. On the bottom, a simulation of the (4, 3) band is shown inverted that has been computed by the pgopher program developed by Western [35] and using molecular constants from Tanabashi et al [20,25]. As mentioned above, a global analysis of the rotational perturbations has not been performed and is neglected in the simulation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…43 These Swan bands are well known in carbon-rich plasma spectra originating from several sources, including high-speed impacts, the ablation of graphite, the electrical discharge of acetylene, or chemical vapor deposition. 8,10,[47][48][49][50][51] Schultz et al previously examined spectral signatures from oblique impacts into porous particulates and found evidence that Swan band emission can originate from hydrocarbon bearing targets or from the dissociation of carbon-rich compounds under low atmospheric pressure conditions. 10 Additional work by Sugita and Schultz investigated impacts of polycarbonate on water and yielded strong C 2 Swan band emission, which they attributed to a high-temperature carbon-rich vapor that was ablated from rapidly moving, fine-grain fragments in the expanding impact-induced vapor cloud.…”
Section: Fig 15mentioning
confidence: 99%